Birth date predicts alternative life-history pathways in a fish with sequential reproductive tactics - Fagundes, Teresa (2016)
1. In species with plastic expression of alternative reproductive tactics (ARTs), individuals of the same sex, usually males, can adopt different reproductive tactics depending on factors such as body size. 2. The ‘birth date hypothesis’ proposes that condition-dependent expression of ARTs may ultimately depend on birth date, because individuals born at different times of the year may achieve different sizes and express different reproductive tactics accordingly. However, this has rarely been tested. 3. Here, we tested this hypothesis in a fish with ARTs, the peacock blenny (Salaria pavo). A long-term (6 years) mark–recapture study demonstrated that ARTs in the peacock blenny were sequential and that males may follow at least two alternative life-history pathways: a nestholder pathway, in which males express the nest-holder tactic from their first breeding season onwards, and a parasitic pathway, where males reproduce on their first breeding season as sneaker males and subsequently as nest-holders. 4. We have found evidence of a birth date effect on the expression of ARTs in the peacock blenny. Males following the nest-holder pathway are born earlier and are larger at the first breeding season than males following the parasitic pathway, but they have similar growth curves. 5. The mechanisms underlying a birth date effect are far from clear and might be diverse. We have not found support for a mechanism of body size threshold triggering sexual maturation and subsequent ARTs. A mechanism of tactic determination that is strictly based on timing of first maturation is also unlikely. 6. A proxy of lifetime reproductive success shows crossing (body size associated) fitness curves for the two main life-history pathways.